A multi-ancestry genome-wide association study identifies novel candidate loci in the RARB gene associated with hypertensive disorders of pregnancy - Jasmine A. Mack; Adam Burkholder; Farida S. Akhtari; John S. House; Ulla Sovio; Gordon C.S. Smith; Charles P. Schmitt; David C. Fargo; Janet E. Hall; Alison A. Motsinger-Reif (HGG Advances)
Summary: Genetic factors related to pregnancy-related traits are understudied, especially in ancestrally diverse cohorts. To assess maternal contributions to hypertensive disorders of pregnancy (HDP), we performed a multi-ancestry genome-wide association study (GWAS) of HDP in data from the North Carolina-based Personalized Environment and Genes Study (PEGS) cohort with validation in the UK Biobank (UKBB). The GWAS revealed two maternal loci associated with HDP at the genome-wide significance level. The lead independent variants were rs114954125 on chromosome 2 (near LRP1B; odds ratio [OR] [95% confidence interval CI]): 2.96 [2.02–4.34]; p = 2.82 × 10−8) and rs61176331 on chromosome 3 (on RARB; OR (95% CI): 3.08 (2.12–4.48); p = 3.52 × 10−9). We validated the associations near RARB with a meta-analysis of PEGS and the UKBB. We also identified cis-expression quantitative trait loci in the candidate region associated with decreased RARB expression in macrophage cells exposed to Salmonella. Chromatin mapping in FUMA identified a significant interaction within chromosome 3’s enhancer and open chromatin regions, with strong effects observed for RARB and H3P10 gene regulation in mesendoderm cells, mesenchymal stem cells, and trophoblast-like stem cells. We applied existing polygenic scores (PGS) for preeclampsia and gestational hypertension and found that the scores were significantly associated with HDP in PEGS. The findings demonstrate the power of multi-ancestry studies for genetic discovery and highlight the relationship between immune response, regulation, and HDP and the utility of PGS for risk prediction. (PEGS is registered at ClinicalTrials.gov: NCT00341237.)